Updates in novel immunotherapeutic strategies for relapsed/refractory AML - Bawek, Sawyer; Gurusinghe, Sayuri; Burwinkel, Matthew; Przespolewski, Amanda (Frontiers in Oncology, 2024)
Acute myeloid leukemia (AML) is a severe hematological malignancy with poor outcomes, particularly in older adults. Traditional treatment options like high-dose chemotherapy often lead to refractory or relapsed AML, with even worse outcomes. New therapies for relapsed and refractory AML are needed, and this review explores the most recent advancements in immunotherapy in AML. Checkpoint Inhibitors utilizing innate or adaptive immune targeting have shown potential to improve AML outcomes when combined with hypomethylating agents and chemotherapy. The use of adoptive cell therapy in AML demonstrates promising early data, however, there is a need for better target selection. Although early in development, both vaccine therapy as well as stimulator of interferon genes (STING) agonists have potential to enhance the innate immune response to overcome AML’s immune evasion. Immunotherapy has become a promising approach for AML treatment, especially in refractory and relapsed AML, especially in patients who are not eligible for allogeneic stem cell transplants. Future research should focus on a deeper understanding of the immune microenvironment to identify the most critical targets for optimization, as well as personalized therapeutic combination strategies. Here we present a comprehensive overview of the recent developments in immunotherapy for relapsed and refractory AML.